The Role of the Working Capital Structure in Financing Innovation: Evidence from the Eastern European Countries - Ben Flah, Ines; Lajmi, Azhaar (Copernican Journal of Finance & Accounting, 2025)
The research objective of the article is to examine the relationship between working capital components and different types of innovation, using a sample of 8,633 companies from 22 Eastern European countries. We resume the main theoretical work concerning the importance of working capital as a financing resource for innovation activities, specifically characterized by high uncertainty and information asymmetries. The applied research method aims to enrich and complete this literature by employing a pooled cross-sectional data from the Business Environment and Enterprise Performance Survey to investigate the Working Capital Structure effect on innovation of firms in Eastern Europe countries. We apply a probit model to investigate the link between innovation and different financial resources in a context that has rarely been explored in previous studies. The outcome of the research indicates that WCS influences differently the various innovation proxies. The main conclusions of this research highlight the importance of working capital as funding resource for innovation activities. It also shows the importance of bank credit in innovation funding. We also find that results diverge across the innovation kinds and business sector.